2019
DOI: 10.2174/1568026619666181130140350
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Assessment of ADME Properties: Advances in Caco-2 Cell Monolayer Permeability Modeling

Abstract: One of the main goals of in silico Caco-2 cell permeability models is to identify those drug substances with high intestinal absorption in human (HIA). For more than a decade, several in silico Caco-2 models have been made, applying a wide range of modeling techniques; nevertheless, their capacity for intestinal absorption extrapolation is still doubtful. There are three main problems related to the modest capacity of obtained models, including the existence of inter- and/or intra-laboratory variability of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 134 publications
1
24
0
Order By: Relevance
“…Finally, we also predicted the passive transmembrane permeation using Caco-2 cell monolayers or MDCK cells as models. Currently, both models are used as a simplified in vitro model for intestinal absorption in drug development (Broccatelli et al, 2016;Pham-The et al, 2018;Press & Di Grandi, 2008). Our results showed that in comparison with reference drugs, Speciophylline, Uncarine F and Uncaric acid have 72-342 nm/s.…”
Section: Ligandmentioning
confidence: 78%
“…Finally, we also predicted the passive transmembrane permeation using Caco-2 cell monolayers or MDCK cells as models. Currently, both models are used as a simplified in vitro model for intestinal absorption in drug development (Broccatelli et al, 2016;Pham-The et al, 2018;Press & Di Grandi, 2008). Our results showed that in comparison with reference drugs, Speciophylline, Uncarine F and Uncaric acid have 72-342 nm/s.…”
Section: Ligandmentioning
confidence: 78%
“…The QikProp software allowed further predictions on pharmacokinetic properties of 4 and 5, based on similarities with those of the 95% of a dataset of known drugs and drug-like compounds, e.g. predicted blockade of hERG K + channels, 31 predicted Caco-2 monolayer permeability, 32 and predicted MDCK monolayer permeability. 33,34 These preliminary predictions (data not shown) indicated that, at therapeutic concentrations, 4 might be expected to cross to the blood-brain barrier via passive diffusion.…”
Section: Drug-likeness Of 4 Andmentioning
confidence: 99%
“…MDCK (nm/s) [h] 316 86 87 % GI [i] 95 Furthermore, hybrid 1 could exhibit a greater human oral gastrointestinal (GI) absorption about 95 %, which may suggest that the small molecule could be absorbed throughout the intestinal segments upon oral administration. To support this data, calculated permeation through Caco-2 cell monolayers or MDCK cells [50][51][52] may also indicate a good permeation for this compound inside the gut epithelial wall, displaying optimal values of 662 and 316 nm/s. In accordance with reference values taken from 95 % of FDA-approved drugs together with that ideal range for lipid-based formulations (À 2.0 to 6.0), [53] 1 could have an optimal lipophilicity value (logP o/w ) of 3.050, which may suggest the ability of the molecule to penetrate the lipid bilayers of the infected cells.…”
Section: In-silico Pharmacokinetic Analysis (Physicochemical and Admementioning
confidence: 84%